Effectiveness of a New App in Improving Oral Hygiene in Orthodontic Patients: A Pilot Study - Raquel Lopes dos Santos; Manuela da Silva Spinola; Ellen Carvalho; Denis Clay Lopes dos Santos; Naile Dame-Teixeira; Debora Heller (Elsevier, 2023)
Objectives: The aim of this randomised clinical trial was to evaluate the effects of a mobile application (app) on the oral hygiene (OH) of adolescents undergoing fixed orthodontic treatment. Methods: Eight volunteers (14-19 years old) were randomly allocated to the experimental or control groups. Volunteers in the control group received standard OH (SOH) instructions, whilst volunteers in the experimental group received SHO + OH guidance and motivation through an app tailor-made for this study. Clinical assessments were made using the visible plaque index (VPI) and gingival bleeding index (GBI) at 5 different time points: before orthodontic device installation (T0); at baseline (T1); and 30 (T2), 60 (T3), and 90 (T4) days after randomisation. Significant differences were evaluated using Student t test and multilevel logistic regression analysis. Results: Although no significant difference could be observed, VPI at T1 and T2 were lower for volunteers in the experimental group (33.20 ± 19.29; 32.10 ± 7.72) than for the volunteers in the control group (42.11 ± 8.56; 43.59 ± 34.71). The same was observed for GBI, in which volunteers in the experimental group presented lower GBI at T1 and T2 (12.70 ± 8.10; 13.72 ± 7.39) than volunteers in the control group (27.53 ± 17.89; 20.38 ± 9.95). Good acceptance for using the app was shown by volunteers. Conclusions: This study shows the potential utility of the mobile app for improving the OH of adolescents.